2014
DOI: 10.1093/neuonc/nou307
|View full text |Cite
|
Sign up to set email alerts
|

Programmed death ligand 1 expression and tumor-infiltrating lymphocytes in glioblastoma

Abstract: TILs and PD-L1 expression are detectable in the majority of glioblastoma samples but are not related to outcome. Because the target is present, a clinical study with specific immune checkpoint inhibitors seems to be warranted in glioblastoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
483
11
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 511 publications
(553 citation statements)
references
References 50 publications
35
483
11
6
Order By: Relevance
“…Furthermore, PD-L1 expression level in the tumor tissue was positively associated with the likelihood of clinical benefit with PD-1 inhibitor in nonsmall-cell lung cancer as well as other tumor types (132,133). A recent study showed robust and diffuse expression of PD-L1 assessed by immunohistochemistry in newlydiagnosed as well as recurrent GBM (88% vs. 72.2%, respectively), which is a relatively high percentage compared to other cancer types such as melanoma (134). Higher expression of PD-L1 in tumor tissue correlated with worse outcome in another study with 94 patients with GBM (135).…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…Furthermore, PD-L1 expression level in the tumor tissue was positively associated with the likelihood of clinical benefit with PD-1 inhibitor in nonsmall-cell lung cancer as well as other tumor types (132,133). A recent study showed robust and diffuse expression of PD-L1 assessed by immunohistochemistry in newlydiagnosed as well as recurrent GBM (88% vs. 72.2%, respectively), which is a relatively high percentage compared to other cancer types such as melanoma (134). Higher expression of PD-L1 in tumor tissue correlated with worse outcome in another study with 94 patients with GBM (135).…”
Section: The Role Of Immune Checkpoint Inhibitors In Glioblastoma Immmentioning
confidence: 99%
“…18,19 Gliomas have been shown to employ a variety of mechanisms to suppress the immune system, such as downregulation of MHC class I molecules, production of transforming growth factor-b (TGF-b), vascular endothelial growth factor (VEGF), prostaglandin E2, and IL-10, expression of ligands of checkpoint receptors, such as PD-1, and accumulation of immunosuppressive cells, such as myeloidderived suppressor cells (MDSCs), regulatory T cells (Tregs), and tumor-associated macrophages (TAMs). [23][24][25][26][27][28][29][30] It has been previously shown in human samples and experimental GBM models that MDSCs are powerful inhibitors of anti-tumor immune responses. 30,31 Through a variety of mechanisms that inhibit T cell activation and expansion, including the production of arginase and inducible nitric oxide synthase (iNOS), reactive oxygen species and/or reactive nitrogen species (ROS and/or RNS), release of IL-10, expansion of regulatory T cells (Tregs), and inhibition of T cell migration, MDSCs have been shown to promote immunosuppression and tumor progression.…”
Section: Malignant Brain Tumors (Gliomasmentioning
confidence: 99%
“…Circulating monocytes from GBM patients express high levels of PDL1 ( Figure 6A). 23,51 Since our data showed that MDSC depletion enhanced the quantity and quality of anti-GBM T cell response, we assessed whether MDSCs from GBM-bearing mice expressed the ligands for CTLA-4 and PD-1. We analyzed the expression of PDL1 and CD80 on tumor-infiltrating and splenic MDSCs.…”
Section: Depletion Of Mdscs Enhances the Tk/flt3l-induced Anti-gbm CDmentioning
confidence: 99%
“…A non-randomized Phase II trial investigated the efficacy of Pembrolizumab for patients with untreated melanoma or non-small cell lung cancer (NSCLC) brain metastasis revealed durable responses in 4 of 18 patients with melanoma and 6 of 18 patients with NSCLC [136]. Given recent data demonstrating PD-1 expression upon tumor-infiltrating lymphocytes, recent clinical trials determining the efficacy of anti-PD-1 or anti-PD-L1 therapy in primary brain tumors are under investigation [137,138]. A phase III trial comparing Nivolumab with bevacizumab and Nivolumab with or without Ipilimumab is currently recruiting patients although a small safety lead-in revealed an overall survival at 6 months of 70% (NCT02017717; Checkmate 143).…”
Section: Immune Checkpoint Therapymentioning
confidence: 99%